2017
DOI: 10.1038/srep40086
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metallopeptidase-2 Gene rs2287074 Polymorphism is Associated with Brick Tea Skeletal Fluorosis in Tibetans and Kazaks, China

Abstract: Brick tea skeletal fluorosis is still a public health issue in the north-western area of China. However its pathogenesis remains unknown. Our previous study reveals that the severity of skeletal fluorosis in Tibetans is more serious than that in Kazaks, although they have similar fluoride exposure, suggesting the onset of brick tea type skeletal fluorosis might be genetically influenced. Here we show that MMP-2 rs2287074 SNP (G/A), but not rs243865, was associated with Brick tea type fluorosis in Tibetans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The fluoride content in tea is thought to be safe and could contribute to human health when the concentration of fluoride at low levels of 100–300 mg kg −1 , but it contained in some special tea (i.e., brick tea) is usually extremely high with levels up to 600 mg kg −1 7 . Brick tea based fluorosis is mainly found in the northwestern of China, such as Qinghai, Tibet, Inner Mongolia, and Sinkiang, where most of minorities are habitual consumer of brick tea with high level of fluoride 8 . To date, brick tea type fluorosis is still considered as a severe health problem in some parts of China, due to it is impossible to change these minorities brick tea habitual consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The fluoride content in tea is thought to be safe and could contribute to human health when the concentration of fluoride at low levels of 100–300 mg kg −1 , but it contained in some special tea (i.e., brick tea) is usually extremely high with levels up to 600 mg kg −1 7 . Brick tea based fluorosis is mainly found in the northwestern of China, such as Qinghai, Tibet, Inner Mongolia, and Sinkiang, where most of minorities are habitual consumer of brick tea with high level of fluoride 8 . To date, brick tea type fluorosis is still considered as a severe health problem in some parts of China, due to it is impossible to change these minorities brick tea habitual consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on SNPs as genetic markers for susceptibility of fluorosis showed that genetic variants in some candidate genes like Collagen type 1 alpha 2 (COL1A2), Calcitonin receptor gene (CTR), Estrogen receptor (ESR), Catechol-o-methyltransferase (COMT), Glutathione Stransferase pi 1(GSTP1), Matrix metallopeptidase 2 (MMP-2), PRL (Prolactin), Vitamin D receptor (VDR), Myeloperoxidase (MPO) and PTH Bst BI could increase or decrease the risk of fluorosis among the exposed individuals in endemic areas [14,15,[30][31][32][33][34][35][36][37]. This present study proposed that a single nucleotide polymorphism in the COL1A2 gene may influence the occurrence of dental fluorosis among children exposed to different concentrations of drinking and cooking waters in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, eight articles (37-44) were excluded because they had unclear demographic data or unclear SF or DF results, or the results were not consistent with the theme. Finally, 15 studies were included in the research: 6 studies (27,35,36,(45)(46)(47) that focused on BTF in Tibetan-inhabited areas were included in group 1; 4 studies (27,45,47,48) that discussed the fluoride content of brick tea were included in group 2 (three articles were included in both group 1 and 2); and 8 articles (38,43,(49)(50)(51)(52)(53)(54) were included in group 3 because they primarily discussed the genetic susceptibility of Tibetans to fluorosis.…”
Section: General Database Statisticsmentioning
confidence: 99%